QUALITY OF PAYMENT SERVICE AND PUBLIC SATISFACTION OF USERS OF USED HOUSEHOLD GAS NETWORKS OF PT. ARUN TOWARDS THE APPLICATION OF MODEL THE TOTAL QUALITY MANAGEMENT (TQM) - Azhari; Ismuhadi; Muhammad Multazam (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
Society needs comfort, tranquility, convenience and satisfaction from all needs and to fulfill their household needs in their daily lives. The purpose of this study is to determine the Quality of Payment Services and Community Satisfaction of Household Gas Network Users (JGRT) of Former PT. Arun Regarding the Application of the Total Quality Management (TQM) Model. The research method used is quantitative with the Ordinary Least Square (OLS) model. The targeted output is to be able to publish in the International Journal of Educational Review, Law and Social Sciences (IJERLAS).